KORELASI NILAI HAMBATAN KONUS (QC) DAN CBR LAPANGAN PADA TANAH LEMPUNG DESA IMBODU - Achmad, Fadly (Jurnal Sainstek, 2011)
The determination of bearing capacity in highway and airport designing is an important element because value of this determination will affect the thickness of its pavement. To determine the bearing capacity, this research used result data from sondir test with Dutch Cone Penetration Test (CPT) and field CBR data used Dynamic Cone Penetrometer (DCP). This research intend to correlate cone resistance (qc) and value of field CBR (DCP). This research located at the construction of Perintis Airport District Pohuwato which has soft soil with relative shallow water table. The result show correlation CBR= 0,14 qc 0,27 qc.